Poisoning by the ingestion of seeds of the fruit of the "cotieira" (Joannesia princeps) - Nishioka, Sérgio de Andrade; Escalante, Rodrigo Dornfeld (São Paulo Medical Journal, 1997)
A 15-year-old boy ingested the core of two seeds of a fruit of Joannesia princeps, a large tree sometimes found planted in sidewalks on streets in Brazilian towns. Four hours after the ingestion, he had several episodes of vomiting and diarrhea, but recovered spontaneously th same day. Poisoning by the ingestion of seeds of Joannesia princeps is possibly not rare, considering that the tree gives plenty of fruit and the seeds have an agreeable flavor, but is probably underestimated as mild cases are unlikely to be reported. Ingestion by small children, that could lead to potentially more severe cases, is in part probably prevented by the hardness of the shells covering the seeds.